High-Temperature Superconductors and Related Compounds Studied by Mössbauer Spectroscopy - E. Kuzmann; Z. Homonnay; S. Nagy; M. Gál; A. Vértes (Active and Passive Electronic Components)
57Fe, 119Sn, and 151Eu Mössbauer spectroscopy was used to study the chemical structure, phonon mode changes, and low-temperature phase transformation around the Tc as well as suppression of superconductivity in high-temperature superconductors and related compounds. Anomalous temperature-dependent changes in the total 57Fe spectral area fraction and in the Mössbauer line shift were simultaneously found around the Tc in a EuBa2(Cu0.9957Fe0.01)3O7-d superconductor. These anomalous changes were attributed to phonon softening and low-temperature phase transformation occurring around the superconducting transition. Significant differences were observed between the 57Fe Mössbauer spectra of superconducting EuBa2(Cu0.9957Fe0.01)3O7-d and the isostructural non-superconducting PrBa2(Cu0.9957Fe0.01)3O7-d. The differences were interpreted in connection with the suppression of superconductivity (by hole filling or hybridization of Pr, Cu and O states) in the Pr-containing compound. The unusually high isomer shift value observed in the Pr-containing material can give evidence for the charge transfer mechanism between the Cu(1) chains and the Cu(2) planes and for its role in the suppression of superconductivity.